Faktor-Faktor Yang Berhubungan Dengan Kejadian Plasenta Previa - Haifa Wahyu; Henni Febriawati; Martika Yosi; Liza Fitri Lina (Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Bengkulu, 2019)
Placenta previa is one of the risks in pregnancy. The purpose of this study was to determine the factors associated with the incidence of placenta previa in Dr. M. Yunus Bengkulu. The research design used was an observational analytic study with a case control approach (case and control). The population in this study were all patients of placenta previa during 2018 in Dr. M. Yunus Bengkulu, as many as 135 people and as many as 74 people were divided into 37 case groups and 37 control groups by purposive sampling technique. Chi Square statistical test results showed the value of Ï for age (p <0,000), parity (p <0,000), history of Caesarean Sectio (p <0.016), history of curettage (p <0.033), and pregnancy distance (p <0.005). In conclusion, based on statistical tests, there is a significant relationship between the factors of maternal age, parity, history of Caesarean Sectio, history of curettage, distance of pregnancy to the incidence of placenta previa. It is recommended to nurses RSUD Dr. M. Yunus Bengkulu to be able to provide education in preventing the occurrence of placenta previa by conducting interviews and discussions with risk patients at RSUD Dr. M. Yunus Bengkulu.KeywordsÂ Â Â Â Â Â : Pregnancy distance, Curettage, Parity, Placenta previa, Sectio Caesarea, Age